Unlearning and consent in the UK Fire and Rescue Service. (December 2022) - Brooks, James; Grugulis, Irena; Cook, Hugh
Why does so much literature on unlearning ignore the people who do the unlearning? What would we understand differently if we focused on those people? Much of the existing literature argues that unlearning can only be achieved, and new knowledge acquired, if old knowledge is discarded: the clean slate approach. This might be a reasonable way of organising stock in a warehouse, where room needs to be created for new deliveries, but it is not an accurate description of a human system. This article draws on a detailed qualitative study of learning in the UK Fire and Rescue Service to challenge the clean slate approach and demonstrate that, not only did firefighters retain their old knowledge, they used it as a benchmark to assess new routines and practices. This meant that firefighters' trust in, and consent to, innovation was key to successful implementation. In order to understand the social aspects of unlearning, this research focuses on the people involved as active agents, rather than passive recipients or discarders of knowledge.